2015
DOI: 10.30958/ajss.2-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Self-Classified Religious and Spiritual Emerging Adults: Conceptual and Operational Challenges

Abstract: The last ten years has witnessed a sharp increase in research related to spirituality as well as the proliferation of numerous measures of the construct. However, there has been little research examining the relationship between and among measures of spirituality, much less to measures of religion. This study sought to determine whether measures of spirituality and religion could discriminate between participants who self-identified as both religious and spiritual (B), religious only (R), spiritual only (S), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Relatedly, it may be that university students do not integrate institutionalized religion and acceptance of others (item 14) and selfless caring (item 13), as these two items loaded most strongly onto Selflessness. University students may be prone to identify as "spiritual, but not religious," making the differentiation between religiosity and spirituality in this population difficult (Handal et al 2014;Handal et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, it may be that university students do not integrate institutionalized religion and acceptance of others (item 14) and selfless caring (item 13), as these two items loaded most strongly onto Selflessness. University students may be prone to identify as "spiritual, but not religious," making the differentiation between religiosity and spirituality in this population difficult (Handal et al 2014;Handal et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary concepts of spirituality and religiosity presuppose that both constructs overlap (Koenig, 2009;Zinnbauer & Pargament, 2005), which makes their psychometric demarcation difficult (Kapuscinski & Masters, 2010). Handal et al (2015Handal et al ( , 2017 have tried to verify to what extent spirituality and religiosity were mutually independent. The authors concluded that there was a significant convergence between measures.…”
Section: Introductionmentioning
confidence: 99%